Modern survey sampling - Chaudhuri, Arijit (Boca Raton CRC Press, Taylor & Francis Group, 2014)
Starting from the preliminaries through live examples, the author tells the story about what a sample intends to communicate to a reader about the unknowable aggregate in a real situation. The story develops its own logic and a motivation for the reader to put up with, herein follows. Various intellectual approaches are set forth, in as lucid a manner as possible. Developments reached hitherto are presented and reviewed. Certain fresh and unseen problems are also noted and possible solutions are hit upon"-- Provided by publisher. "Preface At last this is my venture to address a textbook on Sample Surveys to an international readership. This is meant for the students of the tender ages at the under-graduate level university courses in statistics and also for the slightly maturer courses at the graduate and master levels in statistics. The present author has an elementary level textbook called "Essentials of Survey Sampling" published by Prentice Hall of India in New Delhi in January, 2010 and with 1000-odd reprints in September, 2013 and is supposed to go for a revised second edition in early 2014. "Survey Sampling : Theory & Methods" is by the present author in collaboration with Professor H. Stenger of Mannheim University, Germany with the first edition in 1992 by Marcel Dekker, USA and a thoroughly revised and hugely enhanced second edition by Chapman & Hall / CRC, Taylor & Francis Group, Boca Raton, USA in 2005. All these three specimens bear quite a sizeable material on various aspects of survey sampling indeed. Yet, a need is felt for what may be called really an international level textbook on survey sampling despite there being quite a few book level publications available in the international market on the present subject. As I have been teaching this subject over numerous years now in Indian Statistical Institute with a considerable experience outside as well, having published profusely as scattered in numerous journals it seems there is some justification to expect some attention from the curious public around the world to hear what this veteran teacher has to say. Applied Statistics Unit Arijit Chaudhuri Indian Statistical Institute, email: arijitchaudhuri1@rediffmail.com 203, B.T. Road, mobile: (0)9830740074 Kolkata - 700 108, India. November, 2013.
Includes bibliographical references (pages 245-254) and indexes.
Keywords: Sampling (Statistics)